GIS and Remote Sensing-based Evaluation of Vegetation Diversity due to Topography in Semi-Arid Environment - Al-Sababhah, Noah; Hazaymeh, Khaled (Dirasat: Human and Social Sciences, 2019)
This study aims at investigating the possible relation between topography and the spatial distribution of vegetation cover within a semi-arid environment in Irbid region, Jordan. To accomplish this, various topographic variables including elevation, slope, and aspect; and land cover distribution within the study area are used. The methodology comprised a spatial analysis of digital elevation data (i.e., ASTER-GDEM) and remote sensing data (i.e., Landsat8 images). In terms of vegetation cover distribution; (the same before) five major types including: forest, field crops, vegetables, tree crops, and pastures were identified.Through the results, (the same before) a strong relation between topography and vegetation cover diversity in Irbid governorate could be identified. Several environmental factors are proposed that might overprint the topography-vegetation cover association. Overall, this study expands the geographic context of the link between topography and vegetation cover in semi-arid environment, while also demonstrating the utility of remote sensing and GIS in environmental modeling.